Thermal barrier and temperature sensing dual-function integrated garnet ceramic material as well as preparation method and application thereof

By modifying Y3Al5O12 with a garnet structure to a high entropy and doping it with luminescent ions, a high entropy ceramic matrix is ​​formed, which solves the problems of mismatch in thermal expansion coefficients and limited upper limit of temperature measurement. This achieves the integration of dual functions of thermal barrier and temperature sensing, improves the thermal barrier performance and temperature sensing performance of the material, simplifies the structure, and improves the reliability and lifespan of the material.

CN120841947APending Publication Date: 2025-10-28XIAMEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510943818.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-10-28

Smart Images

  • Figure CN120841947A_ABST
    Figure CN120841947A_ABST
Patent Text Reader

Abstract

The invention discloses a thermal barrier and temperature sensing dual-function integrated garnet ceramic material as well as a preparation method and application thereof. The material is composed of a high-entropy matrix of a garnet structure and luminescent ions, and the crystal structure is the same as that of Y3Al5O12. The thermal barrier properties such as thermal conductivity, sintering resistance, corrosion resistance and mechanical properties of the material are improved through the high-entropy design. And meanwhile, temperature sensing is realized by utilizing the change of different emission peaks generated by luminous ions along with the temperature, a non-thermal coupling energy level fluorescence intensity ratio technology of different luminous centers breaks through the limitation of the traditional thermal coupling energy level, the difference of thermal quenching behaviors is enhanced through energy transfer, and the temperature measurement upper limit and the sensitivity are cooperatively improved. In addition, the preparation method has the advantages of high sintering speed, controllable grain growth and the like, and is beneficial to low thermal conductivity and excellent mechanical properties. The material is of an integrated structure, the problems of interface stress concentration and the like are solved, the reliability and the service life of the hot end component are remarkably improved, and the material has wide application prospects in turbine blades and other hot end components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical temperature sensing technology for thermal barrier materials, specifically to a garnet ceramic material with integrated thermal barrier temperature sensing and its preparation method and application. Background Technology

[0002] As modern advanced engines and gas turbines develop towards higher operating temperatures, the lifespan of their hot-end components, such as turbine blades, faces severe challenges. To alleviate this problem, thermal barrier materials are typically coated onto the surface of these components to reduce surface temperature and thus extend their lifespan. However, in high-temperature environments, even small temperature deviations can easily lead to component failure and other safety hazards. Therefore, a temperature sensing layer needs to be added to the surface of the thermal barrier layer for real-time temperature monitoring. However, the difference in thermal expansion coefficients between the thermal barrier layer and the temperature sensing layer can cause interfacial stress concentration, easily leading to cracking or detachment of the functional layers. Furthermore, adding multiple layers increases the weight of the component, which is detrimental to the thrust-to-weight ratio. Therefore, merging functional layers and simplifying the structure is of significant scientific importance.

[0003] In recent years, optical temperature sensing technology has attracted widespread attention due to its non-contact measurement, anti-interference, and high reliability. By doping existing thermal barrier materials with suitable luminescent ions, dual functions of thermal barrier and temperature sensing can be achieved simultaneously in a single material. However, the most widely used thermal barrier ceramic material is yttrium-stabilized zirconia (YSZ), which suffers from poor phase stability, poor sintering resistance, and susceptibility to corrosion, making it difficult to meet the ever-increasing performance requirements. Therefore, the development of novel thermal barrier materials is urgently needed. Garnet-structured Y3Al5O 12 It possesses advantages such as high melting point, good stability, strong resistance to sintering, excellent optical properties, and ease of doping, making it one of the candidate materials for thermal barrier ceramics and optical matrices. However, it also has disadvantages such as high thermal conductivity and low coefficient of thermal expansion. Furthermore, most current optical temperature sensing materials are limited by the thermal quenching effect of luminescent ions and the thermal coupling energy level difference, generally facing upper limits on temperature measurement and relative sensitivity (S). r The problem of difficulty in synergistic improvement exists. Therefore, there is an urgent need to develop novel structural-functional integrated materials that combine thermal barrier and temperature sensing properties, and excel in both aspects. Summary of the Invention

[0004] The purpose of this invention is to overcome the above-mentioned shortcomings of the prior art and provide a garnet ceramic material with integrated thermal barrier and temperature sensing functions, its preparation method and application.

[0005] To achieve the aforementioned objectives, in a first aspect, the present invention provides a garnet ceramic material with integrated thermal barrier and temperature sensing functions. This material is produced by synthesizing Y3Al5O4 garnet structure. 12It is obtained by high-entropy modification and doping with luminescent ions to achieve temperature-dependent luminescence, and can simultaneously possess the dual functions of thermal barrier and temperature sensing. Its general chemical formula is Re. 3- a Al5O 12 :aX. Among them, in order to form with Y3Al5O 12 For high-entropy matrices with the same crystal structure, Re should include 5 or more types of Y with similar radii that can occupy Y. 3+ The matrix contains trivalent rare earth ions at lattice sites, with each ion comprising the matrix having a content of ≥0.15% and a dopant content of ≥1.05%. X, as the dopant luminescent ion, should contain two or more types of ions, and each luminescent ion should be doped into Y3Al5O4. 12 This will not lead to a second phase, and when the content of a certain ion is ≥0.15 and they all occupy Y... 3+ When at a lattice site, this ion can also participate in the composition of a high-entropy ceramic matrix, becoming a component of Re.

[0006] In one implementation, high-entropy modification improves one or more aspects of thermal barrier performance. This includes reduced thermal conductivity, altered coefficient of thermal expansion, improved resistance to sintering, enhanced corrosion resistance, and improved mechanical properties.

[0007] In one embodiment, the doped luminescent ions include, but are not limited to, two or more of the rare earth ions, transition metal ions, and main group metal ions that can be incorporated into a high-entropy ceramic matrix to produce significant luminescence. Furthermore, the selected multiple ions can be excited by the same excitation light source, and the emission peaks produced do not overlap and exhibit temperature dependence.

[0008] In one embodiment, the energy difference ΔE between the various doped luminescent ions is greater than 2000 cm⁻¹. -1 The non-thermally coupled energy levels formed can surpass the traditional thermally coupled energy levels (ΔE < 2000 cm⁻¹). -1 While the sensitivity of these luminescent centers is theoretically limited, they also possess mechanisms such as energy transfer / cross-relaxation. These mechanisms can be utilized to reduce the thermal quenching effect and amplify the differences in thermal quenching behavior among different luminescent centers, thereby extending the upper limit of temperature measurement (≥600K) and improving sensitivity (maximum S). r ≥0.3% K -1 ).

[0009] Secondly, the present invention provides a method for preparing a garnet ceramic material with integrated thermal barrier and temperature sensing functions, comprising:

[0010] The first step is to weigh high-purity (≥99.99%) alumina, at least 5 kinds of rare earth oxide raw materials and at least 2 kinds of luminescent oxide raw materials (such as europium oxide, cerium oxide, manganese oxide, etc.) according to the stoichiometric ratio, and add them together with sintering aid, dispersant, dispersion medium and ball milling pellets. Then transfer them to a ball milling jar and ball mill them at a speed of 250-450 r / min for 20-40 h.

[0011] The second step is to dry the ball-milled slurry in an oven at 60-150℃. After drying, the material is ground in an agate mortar and sieved through a 150-300 mesh screen to obtain a fine powder.

[0012] The third step is to dry press the powder into shape using a mold with a diameter of 10-18mm, then place it in a muffle furnace for pre-firing and debinding, then seal it and place it in a cold isostatic press, where isotropic high pressure is applied through a medium of water or oil to achieve uniform densification, thereby obtaining a ceramic green body.

[0013] The fourth step involves placing the ceramic green body in a Joule heating furnace for high-temperature rapid sintering to obtain a garnet ceramic material with both thermal barrier and temperature sensing functions.

[0014] In one embodiment, the dispersant used in the first step to prevent particle agglomeration and promote uniform dispersion is ammonium citrate (C6H4O2). 17 The raw materials are N3O7 or polyethylene glycol, with a content of 0.5-3% of the total mass of the raw materials. The sintering aid used to reduce the sintering temperature and promote densification is tetraethyl orthosilicate (Si(OC2H5)4), with a content of 0.1-2% of the total mass of the raw materials. The dispersion medium is ethanol or water. The grinding balls are alumina or zirconia grinding balls, with a mass ratio of grinding balls to total raw materials of 9-15:1. The grinding balls are a mixture of two different sizes of grinding balls, with diameters of 3-7 mm and 1-3 mm, and a mass ratio of grinding balls of 3-5:1.

[0015] In one embodiment, in order to make the ceramic green body dense and free from cracks, the dry pressing pressure in the third step is 250-600 MPa, the glue removal temperature is 600-900℃, the glue removal time is 5-10 h, the cold isostatic pressing pressure is 200-300 GPa, and the holding time is 100-200 s.

[0016] In one embodiment, in order to achieve dense sintering of the material, the fourth step involves using a Joule heating furnace under vacuum conditions to reach a sintering temperature of 1500-1900°C for 10-30 seconds, with a sintering time of 10-60 seconds.

[0017] Thirdly, the present invention provides an application of a thermal barrier temperature sensing dual-function integrated garnet ceramic material in turbine blades and related hot-end components, wherein the material is coated on the surface of the turbine blade.

[0018] The advantages and beneficial effects of this invention compared to the prior art are as follows:

[0019] (1) This invention relates to garnet-structured Y3Al5O4, which has advantages such as high melting point, good stability, strong anti-sintering ability, excellent optical properties, and easy doping. 12 The material undergoes high-entropy modification and is doped with luminescent ions, enabling it to simultaneously possess both thermal barrier and temperature sensing functions. This method of merging functional layers simplifies traditional multilayer structures, reduces weight, and solves the problem of cracking or detachment caused by the mismatch in thermal expansion coefficients between the thermal barrier layer and the temperature sensing layer.

[0020] (2) This invention utilizes high-entropy engineering in Y3Al5O 12 The introduction of multiple principal components into Y3Al5O4 resulted in significant high-entropy effects, lattice distortion effects, and hysteretic diffusion effects. These effects synergistically reduced the thermal conductivity and increased the coefficient of thermal expansion of the material, effectively compensating for the inherent properties of Y3Al5O4. 12 However, these effects also enhance the material's resistance to sintering, corrosion resistance, and mechanical properties, overcoming its limitations in thermal barrier performance. These superior characteristics result in a longer service life and better reliability in harsh environments.

[0021] (3) In this invention, multiple luminescent ions are doped into garnet-structured high-entropy ceramics as luminescent centers. The non-thermally coupled energy levels composed of different luminescent centers break through the theoretical limitation of the traditional thermally coupled energy level difference. At the same time, by utilizing the energy transfer and cross-relaxation mechanisms between different luminescent centers that affect luminescence, the thermal quenching effect of the luminescent centers can be effectively suppressed, and the difference in thermal quenching behavior between different luminescent centers can be expanded, thereby achieving a synergistic improvement in the upper limit of temperature measurement and sensitivity.

[0022] (4) This invention uses a Joule heating furnace to sinter garnet ceramic materials. This method has a fast heating / cooling rate, which can achieve ultra-fast (second-level) ceramic sintering, greatly shortening the preparation cycle and saving energy. At the same time, ultra-fast sintering can also effectively inhibit the growth of ceramic grains and obtain a fine and uniform microstructure, which is conducive to achieving low thermal conductivity and excellent mechanical properties of the material. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the integrated thermal barrier layer and temperature sensing layer disclosed in this invention.

[0024] Figure 2 This is a schematic diagram illustrating the principle of the high-entropy design and light-emitting design of the present invention.

[0025] Figure 3 The (Y) prepared in Example 1 0.2 Gd 0.2Tb 0.2 Lu 0.2 Yb 0.2 ) 2.985 Eu 0.015 Al5O 12 XRD pattern of ceramic materials.

[0026] Figure 4 The thermal conductivity curve is shown for the ceramic material prepared in Example 1.

[0027] Figure 5 The curve of the coefficient of thermal expansion of the ceramic material prepared in Example 1 is shown.

[0028] Figure 6 The grain size changes of the ceramic material prepared in Example 1 after being kept at 1723K for different times.

[0029] Figure 7 The image shows a scanning electron microscope (SEM) image of the cross section of the ceramic material prepared in Example 1 after being etched by CMAS at 1623 K for 7 hours.

[0030] Figure 8 The image shows a scanning electron microscope image of the Vickers hardness indentation on the surface of the ceramic material prepared in Example 1, obtained by holding the pressure at 4.98 N for 15 s.

[0031] Figure 9 The excitation spectra of the ceramic material prepared in Example 1 under excitation at 543 nm and 710 nm are shown.

[0032] Figure 10 The emission spectrum of the ceramic material prepared in Example 1 under 285 nm excitation is shown.

[0033] Figure 11 The fluorescence decay curve at 543 nm is monitored for the ceramic material prepared in Example 1 under 285 nm excitation.

[0034] Figure 12 The emission spectrum of the ceramic material prepared in Example 1 is the temperature-dependent emission spectrum from 298K to 1000K under 285nm excitation.

[0035] Figure 13 The integral intensity and integral intensity ratio (I) of the different emission peaks of the ceramic material prepared in Example 1. 543 nm / I 710 nm The variation with temperature and the corresponding fitting curve.

[0036] Figure 14 The absolute sensitivity (S) of the ceramic material prepared in Example 1 a ) and relative sensitivity (Sr (Changes with temperature)

[0037] Figure 15 This is a comparative analysis of the thermal barrier properties of the ceramic materials prepared in Example 1 and Comparative Examples 1-2.

[0038] Figure 16 The upper limit of temperature measurement and S for the ceramic materials prepared in Examples 1 and Comparative Examples 3-5 are given. r A comparative analysis.

[0039] Figure 17 The images show actual photos of the material used in Example 4 on turbine blades, as well as a three-dimensional temperature measurement effect of the surface. Detailed Implementation

[0040] To make the technical problem to be solved, the technical solution, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0041] In a first aspect, the present invention provides a garnet ceramic material with integrated thermal barrier and temperature sensing functions. This material is produced by synthesizing Y3Al5O4 with a garnet structure. 12 By performing high-entropy modification and doping with luminescent ions to achieve temperature-dependent luminescence, a dual-function structure integrating thermal barrier and temperature sensing can be obtained. A schematic diagram of the combined two functional layers is shown below. Figure 1 As shown.

[0042] It consists of a garnet-structured high-entropy ceramic matrix and luminescent ions, with the general chemical formula Re. 3-a Al5O 12 :aX, crystal structure and Y3Al5O 12 The same. Among them, Re includes 5 or more types of radii similarity that can occupy Y. 3+ The lattice site contains trivalent rare earth ions (1.05 ≥ 0.15 of each ion constituting the matrix), and X is a dopant luminescent ion containing two or more types of ions, all of which can be incorporated into Y3Al5O4. 12 This will not lead to a second phase, and when the content of a certain ion is ≥0.15 and they all occupy Y... 3+ When at a lattice site, this ion can also participate in the composition of a high-entropy ceramic matrix, becoming a component of Re.

[0043] Among them, Y3Al5O 12While possessing advantages such as high melting point, good stability, and strong resistance to sintering, its high thermal conductivity and low coefficient of thermal expansion make it less than ideal. However, high-entropy engineering can effectively address this issue. This can be achieved through the application of high-entropy methods in Y3Al5O4. 12 Introducing five or more principal components into a high-entropy system allows for the utilization of the special effects resulting from high entropy (such as high-entropy effect, lattice distortion effect, and hysteresis diffusion effect) to reduce the thermal conductivity, increase the coefficient of thermal expansion, enhance the sintering resistance, improve corrosion resistance, and improve the mechanical properties of the material. These effects can effectively compensate for the shortcomings of Y3Al5O 12 This addresses the shortcomings in thermal conductivity and coefficient of thermal expansion of traditional YSZ ceramics, while further improving other aspects of thermal barrier performance, thus resolving issues such as poor high-temperature phase stability, poor sintering resistance, and poor corrosion resistance. A schematic diagram of the high-entropy design principle can be found below. Figure 2 .

[0044] Furthermore, temperature sensing is achieved by doping a high-entropy garnet-structured ceramic matrix with luminescent ions to induce temperature-dependent emission. However, many current optical temperature sensing materials are limited by the thermal quenching effect of the luminescent ions and the thermal coupling energy level difference, generally facing low temperature measurement limits and S... r The problem of low efficiency. This invention addresses the issue of doping a high-entropy ceramic matrix with two or more types of luminescent ions that produce significant light emission. It utilizes non-thermally coupled energy levels (ΔE>2000cm⁻¹) composed of different luminescent centers. -1 This breakthrough overcomes the traditional thermal coupling energy level difference (ΔE<2000cm). -1 Overcoming the theoretical limitations of traditional luminescence design, and utilizing mechanisms such as energy transfer and cross-relaxation between different luminescent centers that influence luminescence, the thermal quenching effect of luminescent centers is effectively suppressed, and the differences in thermal quenching behavior among different luminescent centers are amplified, achieving a synergistic improvement in both the upper limit of temperature measurement and the sensitivity of temperature measurement. A schematic diagram of the luminescence design principle is shown below. Figure 2 .

[0045] Furthermore, the doped luminescent ions include, but are not limited to, rare earth ions, transition metal ions, and main group metal ions.

[0046] Multiple doped luminescent centers can be excited by the same excitation source, and the emission peaks produced do not overlap and are temperature dependent.

[0047] The doped multiple luminescent centers have mechanisms that affect luminescence, such as energy transfer and cross-relaxation.

[0048] The material can achieve a high upper limit of temperature measurement (≥600K) and high S in temperature sensing. r (≥0.3% K) -1 ).

[0049] Secondly, the present invention provides a method for preparing a garnet ceramic material with integrated thermal barrier and temperature sensing functions, comprising the following steps:

[0050] The first step is to weigh high-purity (≥99.99%) alumina, at least 5 kinds of rare earth oxide raw materials and at least 2 kinds of luminescent oxide raw materials (such as europium oxide, cerium oxide, manganese oxide, etc.) according to the stoichiometric ratio, and add them together with sintering aid, dispersant, dispersion medium and ball milling pellets. Then transfer them to a ball milling jar and ball mill them at a speed of 250-450 r / min for 20-40 h.

[0051] The second step is to dry the ball-milled slurry in an oven at 60-150℃. After drying, the material is ground in an agate mortar and sieved through a 150-300 mesh screen to obtain a fine powder.

[0052] The third step is to dry press the powder into shape using a mold with a diameter of 10-18mm, then place it in a muffle furnace for pre-firing and debinding, and then seal it and place it in a cold isostatic press. Cold isostatic pressing is a powder forming process in which isotropic high pressure is applied to the powder in the sealed mold at room temperature through a liquid or gaseous medium (such as oil or water) to make the powder particles uniform and dense, thereby obtaining a ceramic green body.

[0053] The fourth step involves placing the ceramic green body in a Joule heating furnace for high-temperature rapid sintering to obtain a garnet ceramic material with both thermal barrier and temperature sensing functions.

[0054] Furthermore, the dispersant mentioned in the first step is used to prevent particle agglomeration and promote uniform dispersion; the dispersant is ammonium citrate (C6H4O7). 17 The raw materials are N3O7 or polyethylene glycol, with a content of 0.5-3% of the total mass of the raw materials; the sintering aid is used to reduce the sintering temperature and promote densification, and the sintering aid is tetraethyl orthosilicate (Si(OC2H5)4), with a content of 0.1-2% of the total mass of the raw materials; the dispersion medium is ethanol or water; the ball milling machine is an alumina or zirconia ball milling machine, and the mass ratio of the ball milling machine to the total raw materials is 9-15:1. The ball milling machine is a mixture of two different sizes of ball milling machines, with diameters of 3-7 mm and 1-3 mm, and a mass ratio of 3-5:1.

[0055] Sintering aids are small amounts of substances added during the sintering process of ceramics to lower the sintering temperature, promote densification, and thus improve the mechanical and thermal properties of the material. The content of sintering aids is best between 0.1% and 2% of the total raw material mass. If the content is too low, it is difficult to form a continuous liquid phase or defects, and the sintering aid effect is not significant; if the content is too high, it will lead to an excessive liquid phase, which will weaken the grain boundaries and impair the high-temperature performance.

[0056] The dispersant content is best between 0.5% and 3% of the total raw material mass. If it is too low, it will not be able to completely coat the particle surface, resulting in agglomeration; if it is too high, it will form an excessively thick adsorption layer, which will hinder the close contact of the powder and affect the subsequent sintering.

[0057] The grinding balls are varied depending on the raw materials used. Since alumina is used in this invention, alumina grinding balls are generally used to reduce contamination. The synergistic effect of two grinding ball diameters enables efficient multi-stage grinding, avoiding grinding dead zones or energy waste caused by a single ball diameter. The grinding ball ratio affects the grinding effect and can create a better space-filling model, which is beneficial to the grinding effect. Preferably, the mass ratio of grinding balls to total raw materials is 12:1, and the grinding balls are a mixture of two different sizes, with a mass ratio of 4:1 for grinding balls with diameters of 5mm and 2mm.

[0058] Furthermore, to ensure the ceramic green body is dense and crack-free, the dry pressing pressure in step three is 250-600 MPa, the binder removal temperature is 600-900℃, the binder removal time is 5-10 h, the cold isostatic pressing pressure is 200-300 GPa, and the holding time is 100-200 s. Furthermore, to achieve dense sintering of the material, the sintering temperature in step four is reached at 1500-1900℃ under vacuum conditions in a Joule heating furnace for 10-30 s, and the sintering time is 10-60 s.

[0059] If the dry pressing or cold isostatic pressing pressure is too low, it will easily lead to low green body density, high porosity and low strength after sintering; if it is too high, it will easily lead to particle breakage and microcracks.

[0060] If the temperature and time for debinding are too low, organic residues will contaminate the material; if they are too high, premature sintering and densification, grain growth, etc. will occur.

[0061] If the sintering temperature is too low, the material may not form a pure phase or be dense; if the temperature is too high, the material may melt during the sintering process.

[0062] The Joule heating furnace is a rapid sintering device with a very fast heating rate, reaching over 160℃ / s.

[0063] Thirdly, the present invention provides an application of a garnet ceramic material with integrated thermal barrier and temperature sensing functions in turbine blades and related hot-end components.

[0064] This invention involves spraying phosphor materials of the same composition onto turbine blades to achieve temperature measurement of the turbine blades.

[0065] This invention has undergone numerous experiments, and some of the experimental results are presented here for reference to further describe the invention in detail. The following is a detailed description in conjunction with specific embodiments.

[0066] Example 1

[0067] A method for preparing a garnet ceramic material with integrated thermal barrier and temperature sensing functions includes:

[0068] The first step involves using high-purity (≥99.99%) Y₂O₃, Gd₂O₃, Tb₄O₇, Lu₂O₃, Yb₂O₃, Eu₂O₃, and Al₂O₃ as raw materials, according to (Y 0.2 Gd 0.2 Tb 0.2 Lu 0.2 Yb 0.2 ) 2.85 Eu 0.015 Al5O 12 A total of 10g of raw material was weighed and transferred to a 250mL nylon ball mill jar. Alumina grinding balls with diameters of 5mm and 2mm (mass ratio 4:1) were added. The synergistic effect of the two diameter grinding balls achieved efficient multi-stage ball milling, avoiding grinding dead zones or energy waste caused by a single ball diameter, resulting in better grinding effects. The mass ratio of the grinding balls to the total raw material was 12:1. Anhydrous ethanol, used as the grinding medium, was added in an amount equal to the mass of the powder mixture. 1%wt and 0.5%wt of C6H were added respectively. 17 N3O7 and Si(OC2H5)4 were used as dispersants and sintering aids. Subsequently, the ball mill jar was placed in a ball mill for ball milling at a speed of 320 rpm for 33 hours to obtain a slurry.

[0069] In the second step, after ball milling, the slurry is transferred to a forced-air drying oven and dried at 100°C for 5 hours. After drying, the material is ground and sieved through a 200-mesh sieve to obtain fine powder.

[0070] The third step involves passing the fine powder through a 10mm diameter mold and pressing it at 446MPa for 2 minutes to form a green body. The green body is then debinded at 800℃ for 6 hours. To remove any trapped air, it is then placed in a cold isostatic press and subjected to a cold isostatic pressing process at 250MPa for 3 minutes to obtain the ceramic green body.

[0071] The fourth step involves placing the treated ceramic green body between two layers of carbon cloth and then sintering it rapidly at 1750℃ for 30 seconds under a vacuum of 1.9 Pa in a Joule heating furnace to obtain (Y). 0.2 Gd 0.2 Tb 0.2 Lu 0.2 Yb 0.2 ) 2.85 Eu 0.015 Al5O 12 A garnet ceramic material integrating thermal barrier and temperature sensing functions, its XRD pattern is as follows: Figure 3 As shown.

[0072] The thermal conductivity curve and thermal expansion coefficient curve of the material are as follows: Figure 4 and Figure 5 As shown, its thermal conductivity decreases with increasing temperature, dropping to 2.90 W·m at 673 K. -1 ·K -1 The coefficient of thermal expansion reaches 12.02K. -1 .

[0073] Figure 6 The table shows the grain size variation of the ceramic material prepared in this example after holding at 1723 K for different times. It can be seen that the small grain size contributes to achieving low thermal conductivity and excellent mechanical properties. Meanwhile, as the holding time increases from 2 h to 15 h, the median grain size (D...)... 50 The grain size only increased from 1.03 μm to 1.10 μm, with a grain growth rate of only 7%, exhibiting excellent anti-sintering properties.

[0074] Figure 7 This is a scanning electron microscope image of the cross-section of the ceramic material prepared in this example after being etched by CMAS at 1623K for 7 hours. It can be seen that the etched area is shallow, only about 40μm, and it has good resistance to CMAS corrosion.

[0075] Figure 8 This is a scanning electron microscope image of the Vickers hardness indentation on the ceramic material prepared in this example, obtained by holding the pressure at 4.98 N for 15 seconds. It can be seen that the average diagonal of the indentation is short, indicating a short crack. Calculations show that its average hardness is 15.37 GPa and its average fracture toughness is 1.23 MPa·m. 1 / 2 It has good mechanical properties.

[0076] Figure 9 The excitation spectra of the ceramic material prepared in this example are shown at 543 nm and 710 nm. The spectrum shows a broad absorption band from 250 to 300 nm, with a peak appearing near 285 nm.

[0077] Figure 10 This is the emission spectrum of the ceramic material prepared in this example under 285 nm excitation. The spectrum exhibits multiple emission peaks, with the most significant emission peak located at Tb. 3+ 543nm and Eu 3+ 710nm.

[0078] Figure 11 The fluorescence decay curve at 543 nm for the ceramic material prepared in this example was monitored under 285 nm excitation. It can be seen that as Eu... 3+ With the increase in content, Tb 3+The lifetime at 543 nm gradually decreases, indicating a significant relationship between the two due to Tb. 3+ →Eu 3+ Energy transfer.

[0079] Figure 12 The emission spectrum of the ceramic material prepared in this example is temperature-dependent from 298K to 1000K under 285nm excitation. It can be seen that the intensity of the emission peak gradually weakens with increasing temperature, but there is still a certain luminescence intensity at 1000K, indicating that it can achieve a high upper temperature limit.

[0080] Figure 13 The integrated intensity and integrated intensity ratio (I) of the different emission peaks of the ceramic material prepared in this example. 543 nm / I 710 nm The variation of Tb with temperature and the corresponding fitting curve. It can be seen that Tb 3+ Thermal quenching was significantly lower than that of Eu. 3+ Ions, and the integral intensity ratio (I 543 nm / I 710 nm It exhibits a good parabolic linear relationship with temperature changes and can be used as a temperature sensing parameter.

[0081] Figure 14 S is the ceramic material prepared in this example. a and S r As temperature changes, it can be seen that S a and S r It increases with increasing temperature, reaching its maximum value at 1000K (maximum S). a 32.86% K -1 Maximum S r K is 1.27%. -1 )

[0082] Comparative Example 1

[0083] The preparation method is the same as in Example 1, except that the material is a non-high-entropy structure doped with trace amounts of two types of luminescent ions, and its chemical structural formula is Y. 2.97 Tb 0.015 Eu 0.015 Al5O 12 The raw materials are Y₂O₃, Tb₄O₇, Eu₂O₃, and Al₂O₃, and the sintering temperature is 1775℃. Its thermal conductivity decreases with increasing temperature, but remains above 7 W·m⁻¹ at 673 K. -1 ·K -1 The coefficient of thermal expansion is 11.63 K. -1The grain size is small, with a grain growth rate of 64%, a CMAS etching depth of approximately 60 μm, an average hardness of 14.26 GPa, and an average fracture toughness of 0.64 MPa·m. 1 / 2 .

[0084] Comparative Example 2

[0085] The preparation method is basically the same as in Example 1, except that the material is 8YSZ, and the raw materials are Y2O3 and ZrO4. After sintering, it is annealed in air at 1450°C for 7 hours. Its thermal conductivity increases with increasing temperature, reaching 2.07 W·m at 673 K. -1 ·K -1 The coefficient of thermal expansion is 12.85 K. -1 The grain size is relatively large, with a grain growth rate of 228%. It was completely corroded by CMAS, with an average hardness of 9.13 GPa and an average fracture toughness of 1.13 MPa·m. 1 / 2 .

[0086] Figure 15 This paper presents a comparative analysis of the thermal barrier properties of the ceramic materials prepared in Example 1 and Comparative Examples 1-2. The results show that the sample prepared in Example 1 possesses excellent thermal barrier properties, demonstrating the significant effectiveness of the strategy employed in this invention.

[0087] Comparative Example 3

[0088] Its preparation method is the same as in Example 1, except that this material is doped with only one luminescent center, and its chemical structural formula is (Y 0.2 Gd 0.2 Tb 0.2 Lu 0.2 Yb 0.2 )3Al5O 12 The raw materials are Y₂O₃, Gd₂O₃, Tb₄O₇, Lu₂O₃, Yb₂O₃, and Al₂O₃. Its upper temperature limit is 998K, and its maximum temperature is [not specified in the original text]. r K is 0.09%. -1 .

[0089] Comparative Example 4

[0090] Its preparation method is the same as in Example 1, except that this material is doped with only one luminescent center, and its chemical structural formula is (Y 0.25 Gd 0.25 Lu 0.25 Yb 0.25 ) 2.985 Eu 0.015 Al5O 12 The raw materials are Y₂O₃, Gd₂O₃, Lu₂O₃, Yb₂O₃, Eu₂O₃, and Al₂O₃. Its upper temperature limit is 898K, and its maximum temperature is [not specified in the original text].r K is 0.37%. -1 .

[0091] Comparative Example 5

[0092] The preparation method is the same as in Example 1, except that the material has a non-high-entropy structure and a chemical structural formula of (Y). 0.8 Tb 0.2 ) 2.985 Eu 0.015 Al5O 12 The raw materials are Y₂O₃, Tb₄O₇, Eu₂O₃, and Al₂O₃. Its upper temperature limit is 1098 K, and its maximum temperature is [not specified in the original text]. r 1.15% K -1 .

[0093] Figure 16 The upper limit of temperature measurement and S for the ceramic materials prepared in Examples 1 and Comparative Examples 3-5 are given. r The comparative analysis shows that the sample prepared in Example 1 has excellent temperature sensing performance. The high entropy significantly improves the thermal barrier performance of the material, but has little impact on the temperature sensing performance. The strategy adopted in this invention has significant effectiveness.

[0094] Example 2

[0095] Its preparation method is the same as in Example 1, except that the chemical structural formula of this material is (Y 0.2375 Gd 0.2375 Lu 0.2375 Sc 0.2375 Dy 0.05 ) 2.94 Eu 0.06 Al5O 12 The raw materials are Y2O3, Gd2O3, Lu2O3, Sc2O3, Dy2O3, Eu2O3 and Al2O3.

[0096] Example 3

[0097] Its preparation method is the same as in Example 1, except that the chemical structural formula of this material is (Y 0.2375 Gd 0.2375 Lu 0.2375 Sc 0.2375 Dy 0.05 ) 2.94 Sm 0.06 Al5O 12 The raw materials are Y2O3, Gd2O3, Lu2O3, Sc2O3, Dy2O3, Sm2O3 and Al2O3.

[0098] Example 4

[0099] The preparation method before sieving is the same as in Example 1, but the sieving and subsequent steps are different. After grinding, the powder is placed in a muffle furnace and sintered at 1550°C for 5 hours. Subsequently, the synthesized fluorescent powder is ground and sieved through a 200-mesh sieve to obtain fine particles with uniform particle size of approximately 2 micrometers. This is then deposited onto the surface of a turbine blade, using a 385nm LED as the excitation light source. Two high-speed cameras are positioned around the blade to receive and transmit fluorescence information from the blade surface. By analyzing and processing the fluorescence information, temperature sensing of the turbine blade is achieved. See the physical image of the material applied to the turbine blade and the three-dimensional temperature measurement effect diagram. Figure 17 .

[0100] The above description is only for illustrating the detailed method of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A garnet ceramic material with integrated thermal barrier and temperature sensing functions, characterized in that, By analyzing the Y3Al5O structure of garnet 12 By performing high-entropy modification and doping it with luminescent ions to achieve temperature-dependent luminescence, a material with both thermal barrier and temperature sensing functions can be obtained.

2. The garnet ceramic material with integrated thermal barrier and temperature sensing functions according to claim 1, characterized in that, The material consists of a garnet-structured high-entropy ceramic matrix and luminescent ions, and is related to Y3Al5O 12 They have the same crystal structure and the general chemical formula Re. 3-a Al5O 12 :aX.

3. The garnet ceramic material with integrated thermal barrier and temperature sensing functions according to claim 2, characterized in that, The material should contain five or more types of Re with similar radii that can occupy Y. 3+ The matrix consists of trivalent rare earth ions at lattice sites, with each ion comprising the matrix having a content of ≥0.15% and ≥1.05%. X, as a dopant luminescent ion, should contain two or more types of ions, and the doping of each luminescent ion into the crystal structure should not lead to a second phase. Furthermore, when the content of any one of these ions is ≥0.15% and they all occupy Y... 3+ When at a lattice site, this ion can also participate in the composition of a high-entropy ceramic matrix, becoming a component of Re.

4. The garnet ceramic material with integrated thermal barrier and temperature sensing functions according to claim 1, 2, or 3, characterized in that, The luminescent ions include, but are not limited to, two or more of the following: rare earth ions, transition metal ions, and main group metal ions that can be doped into a high-entropy ceramic matrix to produce significant luminescence. Furthermore, the selected multiple ions can be excited by the same excitation source to emit light, and the emission peaks produced do not overlap and exhibit temperature dependence.

5. The garnet ceramic material with integrated thermal barrier and temperature sensing functions according to claim 4, characterized in that, The energy difference ΔE between the various doped luminescent ions is greater than 2000 cm⁻¹. -1 The non-thermally coupled energy levels formed by these energy levels can overcome the sensitivity limitations of traditional thermally coupled energy levels, and they also exhibit energy transfer / cross-relaxation mechanisms.

6. A method for preparing a garnet ceramic material with integrated thermal barrier and temperature sensing functions, characterized in that, The steps include: The first step is to weigh high-purity alumina, at least 5 kinds of rare earth oxide raw materials and at least 2 kinds of luminescent oxide raw materials according to the stoichiometric ratio, and add them together with sintering aid, dispersant, dispersion medium and ball milling ball, and then transfer them to a ball milling jar for ball milling. The second step is to remove the ball-milled slurry and dry it in an oven. After drying, the material is ground in an agate mortar and pestle and then sieved to obtain a fine powder. The third step is to dry press the powder into shape using a mold, then place it in a muffle furnace for pre-firing and debinding, and then seal it and place it in a cold isostatic press to obtain a ceramic green body. The fourth step involves placing the ceramic green body in a Joule heating furnace for high-temperature rapid sintering to obtain a garnet ceramic material with both thermal barrier and temperature sensing functions.

7. The method for preparing the garnet ceramic material with integrated thermal barrier and temperature sensing functions according to claim 6, characterized in that, The dispersant is ammonium citrate (C6H4O). 17 The raw material is N3O7 or polyethylene glycol, with a content of 0.5-3% of the total mass of the raw materials; the sintering aid is tetraethyl orthosilicate (Si(OC2H5)4), with a content of 0.1-2% of the total mass of the raw materials; the dispersion medium is ethanol or water; the grinding ball is an alumina or zirconia grinding ball, with a mass ratio of grinding ball to total raw materials of 9-15:1, and the grinding ball is a mixture of two different sizes of grinding balls, with diameters of 3-7 mm and 1-3 mm, and a mass ratio of grinding balls of 3-5:

1.

8. The preparation method of the garnet ceramic material with integrated thermal barrier and temperature sensing functions according to claim 6, characterized in that, In the first step, the ball mill is operated at a speed of 250-450 r / min for 20-40 h; in the second step, the drying temperature is 60-150℃ and the sieve is 150-300 mesh.

9. The preparation method of the garnet ceramic material with integrated thermal barrier and temperature sensing functions according to claim 6, characterized in that, In the third step, the dry pressing pressure is 250-600 MPa, the glue discharge temperature is 600-900℃, the glue discharge time is 5-10 h, the cold isostatic pressing pressure is 200-300 GPa, and the holding time is 100-200 s; in the fourth step, a Joule heating furnace is used to reach a sintering temperature of 1500-1900℃ under vacuum conditions for 10-30 s, and the sintering time is 10-60 s.

10. The application of a garnet ceramic material with integrated thermal barrier and temperature sensing functions as described in claims 1-5 in turbine blades and related hot-end components.